On an Estimation Method for an Alternative Fractionally Cointegrated Model - Federico Carlini; Katarzyna Lasak (Tinbergen Institute, 2014)
In this paper we consider the Fractional Vector Error Correction model proposed in Avarucci (2007), which is characterized by a richer lag structure than models proposed in Granger (1986) and Johansen (2008, 2009). We discuss the identification issues of the model of Avarucci (2007), following the ideas in Carlini and Santucci de Magistris (2014) for the model of Johansen (2008, 2009). We propose a 4-step estimation procedure that is based on the switching algorithm employed in Carlini and Mosconi (2014) and the GLS procedure in Mosconi and Paruolo (2014). The proposed procedure provides estimates of the long run parameters of the fractionally cointegrated system that are consistent and unbiased, which we demonstrate by a Monte Carlo experiment.
Keywords: C13; C32; 330; Error correction model; Gaussian VAR model; Fractional Cointegration; Estimation algorithm; Maximum likelihood estimation; Switching Algorithm; Reduced Rank Regression